(The Study on effect of cocodust treatment for the implementation as planting media) - Susanto, Eko (Warta Industri Hasil Pertanian, 2007)
Cocodust is one of the waste of coconut industry which consist of some minerals and it has bulky volume, it means that cocodust has much air space whice is good for medium of plantation. Cocodust has been exported to Europe for plantation medium. Unfortunetly that cocodust consist of highly certai mineral which do not need by plant therefore it should be reduce their component as their standard for plantation medium. The experiment of cocodust was carried out by rinsing of cocodust in water to reduce their mineral such as sodium(Na) and dryed it with artificial dryer and sun drying. The result of treated cocodust mixed with different propotion of soil and used to grow capsicum plant. The effect of the use of cocodust in the growing of capsicum plant was observed their height. The result showed that rinsing of cocodust can reduce sodium content about 90%, drying by using rotary dryer can reduce drying time and the best treatment for planting was propotion beetween cocodust and soil was 1:1.